Whistling in the wind?. Issue 4 (25th July 2019) - Duffy, Peter
Abstract : In this comment piece Peter Duffy, Consultant Urological Surgeon, details his personal experience of whistleblowing, including the punitive action and retaliation he received from NHS management and co‐workers.